THE INFLUENCE OF MOOSE ON TREE SPECIES COMPOSITION IN LIESJÄRVI NATIONAL PARK IN SOUTHERN FINLAND - Heikkilä, Risto; Tuominen, Marita (Lakehead University, 2009)
Intensive forest management has promoted a rapid increase in Finland’s moose (Alces alces) population since the 1970s. The main objective of this study was to determine the role of moose browsing in modifying natural processes of protected forests that are influenced by high moose populations in adjacent managed forests. This study occurred in Liesjärvi National Park located in the mid-boreal vegetation region of Finland. Forest stands were sampled with line-plot sampling (50 m² plots at 100 m distances) in the older (OA; 1956) and newer (NA; 2005) parts of the Park. We found that long-term selective browsing in OA retarded the development of young stands in favor of Norway spruce (Picea abies) and low-growing broadleaf species. Browsing in recent years was relatively intensive in NA where young regeneration areas still existed from previous forest management. The most intensive browsing occurred on 18.6 % of trees in NA and 3.1 % in OA; young palatable tree species were taller in NA than OA. Also, in OA the density of preferred aspen (Populus tremula) and rowan (Sorbus aucuparia) trees was relatively low in the height class that produces the dominant tree canopy. Despite short-term intensive browsing, NA appeared better able to recover to a natural forest state. Fecal pellet groups associated with young Scots pine (Pinus sylvestris) and browsing of birch (Betula spp.) and aspen indicated the importance and role of forage quantity and quality on winter range of moose. The amount of consumed new twig biomass was 20-fold greater in NA compared to OA, indicating a difference in the size of the moose population and presumably habitat quality between the areas. The effect of browsing on different tree species was measured at the stand level in OA in an area restored with prescribed burning 11 years previous. Comparative measurements in two exclosures and adjacent open areas indicated that regeneration in the burned area was browsed intensively and growth of young trees was retarded, except spruce. The major ...